Effects of molecular weight on intestinal anti-inflammatory activities of β-D-glucan from Ganoderma lucidum - Liu, Yanfang; Tang, Qingjiu; Feng, Jie; Liu, Jing; Tang, Chuanhong; Yan, Mengqiu; Zhou, Shuai; Liu, Liping; Zhou, Jing; Zhang, Jingsong (Frontiers in Nutrition, 2022)
To investigate the influence of molecular weight (Mw) on the anti-inflammatory activity of β-D-glucan from Ganoderma lucidum, ultrasonic irradiation was applied to treat the β-D-glucan (GLP, 2.42×106 g/mol) solution to obtain two degraded fractions with molecular weight of 6.53×105 g/mol (GLPC) and 3.49×104 g/mol (GLPN). Structural analysis proved that the degraded fractions possessed similar repeated units with the original β-D-glucan. The in vitro anti-inflammatory activity studies showed that all fractions could significantly inhibit LPS-induced expression of cytokines including TNF-α, IL-8, MIF and MCP-1 in Caco-2 cells at certain concentrations. Moreover, GLPC and GLPN exhibited better anti-inflammatory activity than GLPC. The intestinal anti-inflammatory activity evaluated by dextran sulphate sodium (DSS) - induced colitis mice model showed that intragastric administration of GLPN (lower Mw fraction) could significantly recover inflamed tissues of mice. Compared with GLP and GLPC, GLPN exhibited stronger ability to inhibit the secretion of pro-inflammatory cytokines (TNF-α, IL-1β and IL-6). The results revealed that Mw of β-D-glucan influenced its anti-inflammatory activity and decreasing of Mw would improve the activity, which provided evidence for the potential use of β-D-glucan from G. lucidum as anti-colitis ingredients.